THE ROLE OF TECHNOLOGY TOWARDS TEENAGERS PSYCHOLOGY AND BEHAVIOUR EFFECT - Rr. Renny Anggraini; Iskandar Zulkarnain; Firdaus Firdaus; Nani Nani; Hestu Nugroho Warasto (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
The aim of community service is to provide training to participants to develop technology towards teenager psychology and behaviour effect at 83 State Junior High School Jakarta. The method used there are several stages including the preparation phase, which includes initial survey stabilization and determination of locations and targets. After the survey, the location of the implementation and target of the activity participants are determined. The next stage is the implementation phase of Community Services. The stage will be given understanding knowledge and develop technology being useful for teenagers. This session focuses on providing explanation of how teacher can develop technology nowadays. And the last is the training stage with several methods including lectures, questions and answers, and simulations. The results of Community Service are that the participants (teachers) understand more and gain knowledge about develop technology. There are several strategies that can be tried to develop technology, namely 1) Motivation, 2) Delegation and 3) Appreciation. So the teacher does not create products but creates influence.Keywords: Develop Technology